Perceptions, attitudes and challenges about obesity and adopting a healthy lifestyle among health workers in Pietermaritzburg, KwaZulu-Natal province - Patrick Simfukwe; Brian Van Wyk; Charl Swart (AOSIS, 2017)
Background: The prevalence of obesity is reported to be high and increasing among health workers, in both high-income and low-income countries, which in turn is a common risk factor for all non-communicable diseases. This is alarming, as health workers not only serve the community's health needs but should also serve as role models for a healthy lifestyle. It is therefore important that obesity among health workers is addressed and prevented. Objective: The aim of the study was to explore perceptions and attitudes about obesity among health workers in three selected hospitals in Pietermaritzburg, and to identify the barriers to adopting a healthy lifestyle. Methods: An explorative and descriptive qualitative study design was used, utilising in-depth interviews for data collection. A total of 18 health workers from the three selected hospitals in the metropolitan were individually interviewed. Thematic analysis was done, using a priori themes that were derived from the Health Belief Model. Results: All health workers were aware of the negative consequences of being overweight or obese. However, only a few of the participants chose to adopt a healthy lifestyle. Barriers to adopting a healthy lifestyle included institutional as well as attitudinal factors. Conclusion: Public healthcare facilities need to invest in their work force by giving health workers access to physical exercise facilities and affordable healthy food within the hospital. Health organisations should introduce health behaviour change programmes to combat negative established cultural norms among health staff.